The influence of collectivistic personal values on the formation of entrepreneurial intentions. (August 2020) - Hueso, Juan Alberto; Jaén, Inmaculada; Liñán, Francisco; Basuki, Whysnianti
This article analyses the specific role of collectivistic personal values as an antecedent of entrepreneurial intention. While previous studies have focused on individualistic values, the influence of collectivistic values has remained largely ignored. We study this influence on a sample of 413 university students from the United Kingdom and Spain. The results are consistent in both countries, suggesting that an emphasis on collectivistic personal values triggers an indirect, negative effect on entrepreneurial intentions through both personal attitude and perceived behavioural control. However, it also induces an indirect positive effect through subjective norms. The study indicates that not only individualistic values but the complete personal-value structure is influential in explaining the formation of entrepreneurial intentions.